Prognostic value of sarcopenia in aortic valve replacement: a systematic review and meta-analysis - He, Jie (Frontiers in Nutrition, 2025)
ObjectiveThis study aimed to quantify the prevalence of sarcopenia in patients undergoing surgical aortic valve replacement (SAVR) or transcatheter aortic valve replacement (TAVR), and to assess its association with mortality risk.MethodsRelevant studies were identified through searches of the PubMed, Cochrane Library, Excerpta Medica Database (Embase), Web of Science, and China National Knowledge Infrastructure (CNKI) from inception through July 1, 2025. The prevalence of sarcopenia and its 95% confidence interval (CI) were calculated, with heterogeneity evaluated using the I2 statistic. The link between sarcopenia and mortality following SAVR/TAVR was quantified by hazard ratio (HR) or odds ratio (OR) with 95% CI. Statistical analyses were conducted using Stata 11.0.ResultsThirty-eight studies were included, with 6 focusing on patients undergoing SAVR and 32 on those undergoing TAVR. Sarcopenia was defined by skeletal mass index in 16 studies, while only 2 studies adopted criteria combining reduced muscle mass with low muscle strength and/or reduced physical performance. Sarcopenia’s prevalence among SAVR patients was 31.3% (95% CI 25.3–37.6%). In this cohort, sarcopenia was linked to a significantly higher risk of long-term (≥1 year) mortality (HR = 3.10, 95% CI 2.00–4.79, p < 0.001). In contrast, the prevalence of sarcopenia in TAVR patients was 43.7% (95% CI 38.6–48.9%), with sarcopenia also correlating with increased long-term (>2 year) mortality (HR = 1.25, 95% CI 1.09–1.44, p = 0.001). These associations remained consistent across various follow-up durations, definitions of sarcopenia, and ethnic groups.ConclusionDespite the variation in diagnostic criteria, sarcopenia is significantly prevalent in both SAVR and TAVR populations, with a clear association with elevated long-term mortality following these procedures.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024606633.